Adaptabilitas Hukum Islam di Indonesia dalam Berbagai Model - Fahmi Muhammad Ahmadi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2008)
This passage discusses several key points regarding Islamic law in Indonesia: adaptability, dynamism, and ambivalence of the law. The process of adaptability of Islamic law in Indonesia demonstrates the strong flexibility of Islamic law. The dynamism of Islamic law is evidenced by meeting the contemporary needs of society and the institutionalization of customary law as part of Indonesian Islamic law and national legal development. Meanwhile, ambivalence in the law arises due to the persistence of societal elites who are focused on jurisprudence and a bureaucratic system that is often chaotic, disregarding existing regulations.